2021
DOI: 10.1007/s10291-021-01112-3
|View full text |Cite
|
Sign up to set email alerts
|

Tropical cyclone-induced periodical positioning disturbances during the 2017 Hato in the Hong Kong region

Abstract: The tropospheric delay is an important error source in the Global Positioning System (GPS) positioning and navigation applications. Although most of the tropospheric delays can be removed in the double-differencing (DD) positioning mode, their remaining residuals can still contaminate the positioning accuracy and become unpredictable when tropospheric condition encounters severe variations such as during a tropical cyclone (TC) event. We investigated the positioning performance of five baselines with lengths r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In this paper, the delays caused by the troposphere spatial decorrelation is defined as the non-nominal troposphere. According to the present regularity, various troposphere spatial decorrelation events have been observed in local atmospheric abnormal activities (Lawrence et al 2006;Huang and Graas 2007;Guilbert et al 2017;Yu and Liu 2021). For example, an extreme troposphere spatial decorrelation event of approximately 0.4m is observed at the baseline of 5 km in Ohio (Huang et al 2008), which is unacceptable for high-precision navigation.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…In this paper, the delays caused by the troposphere spatial decorrelation is defined as the non-nominal troposphere. According to the present regularity, various troposphere spatial decorrelation events have been observed in local atmospheric abnormal activities (Lawrence et al 2006;Huang and Graas 2007;Guilbert et al 2017;Yu and Liu 2021). For example, an extreme troposphere spatial decorrelation event of approximately 0.4m is observed at the baseline of 5 km in Ohio (Huang et al 2008), which is unacceptable for high-precision navigation.…”
Section: Introductionmentioning
confidence: 67%
“…where 2 t  is the test statistic noise whose standard deviation is approximately three times larger than that of ionosphere-based test statistics proposed by Yu and Liu (2021). It can be found that the test statistic t2 trades the decorrelation monitoring ability by losing part of the measurement accuracy.…”
Section:  mentioning
confidence: 98%
See 1 more Smart Citation
“…However, little research pertaining to the water vapor during the TC events has been carried out. Precipitable water vapor (PWV) is one of important sources for rainfalls and clouds (Bretherton et al., 2004; Lavender & McBride, 2021; S. Yu & Liu, 2021) and one of the critical driving forces for TC genesis and evolution (Mure‐Ravaud, Dib, et al., 2019; Mure‐Ravaud, Ishida, et al., 2019). Accurate PWV information can help increase the probability of detecting TC's genesis (Ejigu et al., 2021; S.‐Y.…”
Section: Introductionmentioning
confidence: 99%